STRENGTHENING RELIGIOUS MODERATION THROUGH LEARNING AQIDAH MORALS: CASE STUDY AT SIDOARJO HIGH SCHOOL - Siti Kholidatur Rodiyah; Laila Badriyah (STAI Ihyaul Ulum Gresik, 2026)
Contemporary global developments characterized by the strengthening of identity polarization, increasing religious extremism, and social fragmentation demand a paradigm transformation in the learning of Islamic Religious Education, especially in the subject of Aqidah Akhlak. The learning approach, which is still dominated by normative-dogmatic patterns, is considered not optimal in fostering critical awareness, social empathy, and moderate attitudes of students. This research aims to explore in depth the implementation of pedagogical innovation of Aqidah Akhlak as a strategy to strengthen religious moderation at the secondary school level, with a case study at Sidoarjo High School. This study uses a qualitative approach with a case study design. Data collection was carried out through participatory observation, in-depth interviews, and study of learning documents, while data analysis used the interactive model Miles, Huberman, and Saldaña. The results of the study show that pedagogical innovations that integrate reflective, dialogical, contextual, and authentic experience-based approaches are able to significantly transform the practice of learning Aqidah Akhlak. This transformation is reflected in the dynamics of classroom interaction that is more dialogical, collaborative, and egalitarian, as well as the increasing internalization of religious moderation values in students. Students show the strengthening of pluralistic awareness, social empathy, conflict resolution skills, and inclusive attitudes in social life. These findings confirm that Aqidah Akhlak pedagogical innovation has the potential to become a strategic framework in strengthening religious moderation at the secondary education level and makes an important contribution to the development of a humanistic and transformative paradigm of moderate Islamic pedagogy in responding to the socio-religious challenges of the 21st century.